Comparative Analysis Of The Financial Performance Of Islamic Banking With Conventional Banking Listing On The Indonesia Stock Exchange For The 2018-2020 Period - Artedjo, Dennis; Ronalda, Willie; Khairani, Rafida (International Journal of Science, Technology & Management, 2022)
Banks present their financial statements and then re-analyze them with financial ratios as a benchmark for their performance to distinguish the performance of Islamic banking from conventional banks. The goal is to test the Comparative Analysis. Financial Performance of Islamic Banking with Conventional Banking Listing on the IDX for the 2018-2020 period. A quantitative approach with two different average tests (Independent Sample Test). With a population of 46 banks listed on the Indonesia Stock Exchange for the 2018-2020 period. The samples were 3 Islamic & conventional banks with 9 data. The results showed that the CAR of Conventional Banks did not have a significant difference and the CAR of Islamic Banks did not have a significant difference. The NPL of Conventional Banks and NPLs of Islamic Banks have significant differences. BOPO Conventional Banks and BOPO Islamic Banks do not have a significant difference. ROA of Conventional Banks and ROA of Islamic Banks does not have a significant difference. Conventional Bank LDR and Islamic Bank LDR have significant differences.